BAYESIAN SPACE MODEL FOR DENGUE TRANSMISSION DYNAMICA IN PUERTO RICO FOR 2014 DATA - Hernández-González, Greivin (2019)
The purpose of this study has been to investigate the dynamics of dengue transmission in the 76 municipalities that make up the main island of Puerto Rico, for weeks 1 to 4 and 32 to 36 of 2014. A Bayesian spatial model was used to study the possible relationship between incidence, socioeconomic, climatic and environmental variables. Once the models are proposed, the settings are compared with indices such as WAIC (Watanabe, 2010), to determine which one represents the data best. It is also determined by the I-Moran index if there is spatial correlation in the residuals, since the existence of the index is an indicator that the adjustment is not good to some extent. Temperature and precipitation data should have been previously interpolated, since the stations that collect them are not in the population centers, to see the calculations the reader may refer to (Hernández-González, 2017).